2020
DOI: 10.3389/fpsyg.2020.02141
|View full text |Cite
|
Sign up to set email alerts
|

Be Aware Not Reactive: Testing a Mediated-Moderation Model of Dark Triad and Perceived Victimization via Self-Regulatory Approach

Abstract: Generally, it is difficult to work efficiently in a toxic environment. Surprisingly, leaders are found to be liable for such toxic atmosphere because they possess certain traits that employees perceive as victimization. This research assesses the relationship between the dark triad (narcissism, Machiavellianism, and psychopathy) and perceived victimization with a focus on the mediating effect of abusive supervision and the moderating effect of mindfulness. For this purpose, we surveyed 274 employees in the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 115 publications
(213 reference statements)
1
14
0
Order By: Relevance
“…Multiple waves (three-time points, with a lag of 2 months in each wave) of data collection were implemented. It has revealed that a 2-month lag is sufficient to reduce common method variances ( Peng, 2013 ; Zhiqiang et al, 2020 ). At baseline (Time 1), 392 employees participated, providing demographic details (e.g., gender, education, and tenure) and ratings of narcissistic tendencies of their supervisor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple waves (three-time points, with a lag of 2 months in each wave) of data collection were implemented. It has revealed that a 2-month lag is sufficient to reduce common method variances ( Peng, 2013 ; Zhiqiang et al, 2020 ). At baseline (Time 1), 392 employees participated, providing demographic details (e.g., gender, education, and tenure) and ratings of narcissistic tendencies of their supervisor.…”
Section: Methodsmentioning
confidence: 99%
“…This leadership trait negatively impacts the voice of employees ( Huang et al, 2020 ), pro-social behavior ( Liu et al, 2017 ), and proactive behavior ( Liao et al, 2019 ). Additionally, the affection and perception of employees are also influenced by narcissistic traits of their leaders, such that workers often report experiencing negative emotions and depression ( Tokarev et al, 2017 ; Braun et al, 2018 ) as well as perceived victimization ( ud din Khan et al, 2020 ) and perceived abusive supervision ( Nevicka et al, 2018a ). On the other hand, leader narcissism has also been shown positive effects on employees.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Those who have high DT traits are more experience a risk for poor health (Carmody et al, 2008;Chambers, Lo, & Allen, 2008;Dekeyser et al, 2008;. Moreover, mindfulness is associated with better physical and mental health and weakens abusive supervision on perceived victimization when the DT traits are the predictors of this relationship (Khan et al, 2020). Studies also indicated that high mindfulness scores might associate with lowering fibromyalgia impact, pain interference, stress, anxiety, depression, and better mental health-related quality of life (Pleman et al, 2019) buffering the effects of perceived stress on anxiety and depression (Bergin and Pakenham, 2016) and could moderate the relation between Antisocial Personality Disorder and aggression (Taubner et al, 2013;Velotti & Garofalo, 2015).…”
Section: Mindfulness As a Moderatormentioning
confidence: 99%
“…Subsequently, Bozeman et al ( 1996 ) identified the impact of POP on various job outcomes. Scholars identified that work stressors affect adversely the job outcomes of workforce (Sarfraz et al, 2019 ; Sarwar et al, 2019 ; Khan et al, 2020 ). Given this, the burgeoning literature on POP presents mixed findings related to POP and work-related outcomes (e.g., Ferris and Kacmar, 1992 ; Miller et al, 2008 ; Chang et al, 2009 ; Abbas et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%